Cavitation due to Rarefaction Waves and the Reflection of Shock Waves from the Free Surface of a Liquid - Sam, Justin Shang (My University, 2006)
Cavitation was generated in tap water samples by the transmission of tension waves into the liquid, using a hydrodynamic shock tube. The liquid cavitated at absolute negative pressures of about -1 bar. Simulations of bubble responses showed qualitative agreement with experimental observations of oscillatory growth and collapse cycles. Pressure records showed secondary pressure pulsations, confirming the oscillatory nature of the collapse at each rise in pressure. More quantitative comparison of theory and photographic records would require a camera with a higher capture rate. Experiments using another experimental facility involved liquid compression waves with peak static pressures of up to about 1 MPa, which were transmitted from a conventional gas shock tube into a liquid section and were intended to be reflected at the free surface as expansion waves. These experiments were unsuccessful in producing absolute negative pressures or cavitation that was visible through an optical observation section. This was attributed to transition layer effects and pulse attenuation, which contributed to lowering of the peak negative pressure behind the expansion wave, as well as the depth of the transducer and observation section below the free surface, which may have been too low for the peak tension to be superimposed on the lower pressure behind the incident compression wave. Pressure records suggested that, for lower driver pressures, cavitation occurred below the observation section, although this could not be verified optically.
Student Number : 9910049F - MSc (Eng) dissertation - School of Mechanical, Industrial and Aeronautical Engineering - Faculty of Engineering and the Built Environment
Keywords: cavitation; rarefaction; waves; shock; free surface; liquid